Taxonomic and functional diversity of subtidal benthic communities associated with hard substrates at Crozet archipelago (sub-Antarctic, Southern Ocean) - Lelièvre, Yann; Specq, Léa; Lamy, Thomas; Boyé, Aurélien; Downey, Rachel V.; Saucède, Thomas (Frontiers in Marine Science, 2023)
Sub-Antarctic coastal marine ecosystems harbor rich and diverse benthic communities. Despite their ecological uniqueness and vulnerability to global changes, studies on benthic communities remain limited. Using underwater video-imagery, we investigated the taxonomic and functional diversity of benthic communities associated with hard substrates at Baie du Marin (Ile de la Possession, Crozet archipelago). The Baie du Marin species richness and diversity were additively partitioned to evaluate spatial patterns of species through the following spatial scales: within images, among images within transects, and among transects. We analyzed imagery data from seven transects located at different sites inside Baie du Marin and covering contrasting natural rocky habitats and underwater artificial cable substrates. A total of 50 faunal (mainly represented by Echinodermata and Porifera phyla) and 14 algae (mainly represented by Rhodophyta phylum) taxa were identified. Rocky substrates were dominated by high densities of the polychaetes Parasabella sp. and Lanice marionensis, whereas submarine cables were dominated by high densities of the bivalve Kidderia sp. attached to macroalgae. Our results show contrasted distribution patterns in the faunal and algal assemblages within the Baie du Marin, with significant ecological differences between submarine cables and natural rocky substrates. Larger spatial scale (i.e., among transects) accounted for most of the bay richness and diversity, highlighting a high-level of habitat heterogeneity within the bay. Through a trait-based approach, our findings revealed that Crozet benthic communities are characterized by low functional richness, evenness, and redundancy, highlighting a potential vulnerability to current and future natural and anthropogenic changes. This study provides a novel bentho-ecological baseline for future assessments of natural and anthropogenic impacts on the marine environment of the Crozet archipelago; and for the conservation management of these remote habitats that make part of the French Southern Territories Marine Protected Area, recently inscribed on the UNESCO World Heritage list.